Pengaruh Ekstrak Daun Jambu Biji (Psidium guajava, Linn) terhadap Mortalitas Ascaris suum, Goeze in vitro - Tri Adinda Gusvi Meisya; Cr. Siti Utari; Darukutni . (Nexus Biomedika, 2012)
Background: Guava leaves contain tannins and saponins that have been known to have anthelmintic effect. This study aimed to determine the effect of guava leaf extract toward mortality of Ascaris suum, Goeze in vitro Methods: The study was a laboratory experimental research using the post-test only controlled group design. Subjects were adult Ascaris suum, Goeze. The sampling technique used was purposive sampling. Subjects were divided into 7 groups, each group consisting of 5 worms, replication performed 4 times. Saline solution was used in negative control group, pirantel pamoate 5 mg/ml was used in positive control group, while the treatment group used guava leaf extract concentration of 20%, 40%, 60%, 80%, and 100%. Worms were immersed in the test solution at 25 mL and was incubated at 37?. Observations were made every 1 hour for 7 hours and counted the number of dead worms for 7 hours. Data were analyzed with Kruskal-Wallis test, followed by Mann Whitney test and probit analysis. Results: Total number of dead worms after 7 hours of observation in the negative control group was 0, guava leaf extract concentration of 20%, 40%, 60%, 80%, and 100% respectively by 4, 7, 12, 20, and 20, and in the positive control group was 20. Kruskal Wallis test results showed a significant difference, while Mann Whitney test showed some significant and unsignificant differences among those groups (p <0.05 and p> 0.05). Probit analysis showed LC50 and LC90 respectively at concentration 54.320% and 74.516%.. Conclusions: Based on this study, it can be concluded that the guava leaf extract affects mortality of Ascaris suum, Goeze in vitro, the increased concentration of extract increases the number of deaths of worms. Keywords: Guava leaves extract, Ascaris suum